2012
DOI: 10.1186/2193-1801-1-69
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking studies of quercetin and its analogues against human inducible nitric oxide synthase

Abstract: Nitric oxide synthases (NOS) catalyze to produce nitric oxide (NO) from L-arginine. The isoform of NOS i.e. inducible nitric oxide synthases (iNOS) expression is observed in various human malignant tumors such as breast, lung, prostate and bladder, colorectal cancer, and malignant melanoma. Also an increased level of iNOS expression and activity has been found in the tumor cells of gynecological malignancies, stroma of breast cancer and tumor cells of head and neck cancer. Because of its importance in causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 47 publications
1
25
0
7
Order By: Relevance
“…Simulation studies carried out through AutoDock showed quercetin 3-glucoside 7-rhamnoside is a probable anticancerous candidate, confirming the results shown by Discovery Studio. Singh and Konwar also reported previously molecular docking studies of quercetin and its analogues as anticancerous agents [28] . Though all the compounds occupied the similar active site of H-Ras, the evident difference in binding energies may be due to wide structural variations and based on specificity of these natural compounds.…”
Section: Discussionmentioning
confidence: 94%
“…Simulation studies carried out through AutoDock showed quercetin 3-glucoside 7-rhamnoside is a probable anticancerous candidate, confirming the results shown by Discovery Studio. Singh and Konwar also reported previously molecular docking studies of quercetin and its analogues as anticancerous agents [28] . Though all the compounds occupied the similar active site of H-Ras, the evident difference in binding energies may be due to wide structural variations and based on specificity of these natural compounds.…”
Section: Discussionmentioning
confidence: 94%
“…Similar studies have been taken away in the past by many scientists where bioactive compounds are docked on particular receptor to evaluate its affinity [3436]. In our work, we used two approaches of structure based drug designing, namely, molecular docking and pharmacophore modeling for measuring the potential antidiabetic components and their mechanism of activity.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, acacetin also displayed the prominent permissible The amino acid residues (in 1Å distance) were represented in atom types and the hydrogen bonds were denoted in green spheres along with the distance. [34]. Along with the ADME properties the investigation of Lipinski's rule of five has been widely accepted as physicochemical descriptors for predicting the drug-likeliness of a compound.…”
Section: Adme Analysismentioning
confidence: 99%
“…Moreover acacetin comprises the maximum Log value of 2.999. In general, the Log value is a critical factor for the determination of drug absorption within the human body [34].…”
Section: Adme Analysismentioning
confidence: 99%